2011
DOI: 10.1094/mpmi-09-10-0198
|View full text |Cite
|
Sign up to set email alerts
|

An ABC Transporter and a Cytochrome P450 of Nectria haematococca MPVI Are Virulence Factors on Pea and Are the Major Tolerance Mechanisms to the Phytoalexin Pisatin

Abstract: The fungal plant pathogen Nectria haematococca MPVI produces a cytochrome P450 that is responsible for detoxifying the phytoalexin pisatin, produced as a defense mechanism by its host, garden pea. In this study, we demonstrate that this fungus also produces a specific ATP-binding cassette (ABC) transporter, NhABC1, that enhances its tolerance to pisatin. In addition, although both mechanisms individually contribute to the tolerance of pisatin and act as host-specific virulence factors, mutations in both genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 38 publications
(41 reference statements)
1
53
0
Order By: Relevance
“…While most of the MPB-associated fungi can use monoterpenes (i.e., limonene) as a carbon source, one of the Grosmannia cryptic species (Gc from Jeffrey pine) and the saprophyte were unable to. Successful plant and animal pathogens, such as Nectria haematococca and other fungi, use multiple mechanisms for detoxifying plant antimicrobial compounds (41), and our results indicate that this is also the case for Gs. In previous work, we showed that a fungal ABC efflux transporter was a major mechanism by which Gs copes with the diffusion of monoterpenes into its cells in artificial media or when inoculated into young pine trees.…”
Section: Discussionsupporting
confidence: 52%
“…While most of the MPB-associated fungi can use monoterpenes (i.e., limonene) as a carbon source, one of the Grosmannia cryptic species (Gc from Jeffrey pine) and the saprophyte were unable to. Successful plant and animal pathogens, such as Nectria haematococca and other fungi, use multiple mechanisms for detoxifying plant antimicrobial compounds (41), and our results indicate that this is also the case for Gs. In previous work, we showed that a fungal ABC efflux transporter was a major mechanism by which Gs copes with the diffusion of monoterpenes into its cells in artificial media or when inoculated into young pine trees.…”
Section: Discussionsupporting
confidence: 52%
“…Determinants of host specificity and virulence have been identified on ACs of other fungal plant pathogens, including the AC-encoded enzymes for detoxification of a plant phytoalexin in Nectria haematococca (Miao et al . 1991; Coleman et al . 2011) and the virulence-associated host-specific effector genes on lineage-specific chromosomes of Fusarium oxysporum (Ma et al .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there are several examples showing that ABC transporters of plant pathogenic fungi are likewise responsible for the efflux of plant-derived defense compounds. These include atrB of B. cinerea, which transports grapevine (Vitis vinifera) resveratrol, ABC1 of Nectria hematococca, which transports pea (Pisum sativum) pisatin, and ABC-G1 of Grosmannia clavigera, which transports pine (Pinus contorta) monoterpenes (Schoonbeek et al, 2001;Coleman et al, 2011;Wang et al, 2013).…”
Section: Nb-abcg1 and Nb-abcg2 Are Abc Transporters Involved In Both mentioning
confidence: 99%